Analisis Perkembangan Kinerja Keuangan PT Bank Negara Indonesia yang Go Public di Bursa Efek Indonesia - Jalil Yusuf Rambe; Darnawaty Darnawaty; Lisra Lisra (Journal Economic Excellence Ibnu Sina, 2024)
This study aims to determine and analyze the development of the financial performance of PT Bank Negara Indonesia which went public on the Indonesian stock exchange in terms of liquidity, solvency and profitability ratios. The research methodology used in this study is descriptive quantitative, which explains the evolution of financial performance on liquidity, solvency and profitability ratios. Analysis of the financial data resulted in the following findings: Financial performance of PT. Bank Negara Indonesia, viewed based on liquidity ratios, shows that the company remains in poor condition when viewed from the quick ratio and the company's cash ratio is not good because it is not below the industry standard average. The company's performance based on the solvency ratio shows poor results, this condition is caused by the results of the Debt to asset ratio (DAR) and Debt to equity ratio (DER) showing that the results for the 2020-2022 period are far above industry standards. Based on the company's profitability ratio, the company is in poor condition because the results of the ratio calculation show that during this period the company's ROI and ROE conditions are below the industry standard average, although the value increases every year, but this does not indicate the company is in good condition.